Dispute Resolution Between Transportation Carrier/Freight Forwarder Services and Exporters Regarding Damage to Goods/Cargo by Sea Line in Medan - Audrey, Fiona; Pakpahan, Kartina; Rizal, Said (International Journal of Business, Law, and Education, 2024)
Sea transportation services that transport certain goods have many problems, for example related to the responsibility of sea transportation services for damage to goods or delays in goods, so these matters must be resolved in forums or dispute resolution institutions. The legal research method used in this research is normative juridical research which is research carried out or aimed only at written regulations with the nature of descriptive analysis research, which is a method that functions to describe or provide an overview of the object under study. The data source used is secondary data with quantitative data analysis. The results of this research are that the carrier must be responsible if loss or damage occurs from the transportation activity. As explained in Article 40 to Article 42 of the Shipping Law, the carrier company is responsible for the safety of the goods or passengers it transports in accordance with the agreement agreed upon by both parties." that the carrier's responsibility for damage to the goods is realized through the provision of compensation in accordance with article 472 of the Commercial Code, the procedures for settling claims from customers in the process of organizing the transportation of goods by sea are usually settled at the port of unloading between the follower and the recipient of the goods. The things that need to be done by the owner of the goods when submitting a claim for compensation is that the sender or recipient of the goods includes a Bill of Lading and a Receipt in submitting a claim for compensation